Efecto de la aplicación de análogos o antagonistas de GNRH como moduladores de inmunosupresión de hormonas sexuales en lagomorfos - Ramos Sailema, Sandra Del Carmen (2016)
The domestication of the Rabbit (Lagomorphs) has allowed the passage of annual reproduction of non-seasonal type type. However, there are reproductive parameters we evaluate indicate the effect of exogenous drugs. The study of this experiment was to evaluate the effects of the application of GnRH analogues or antagonists establishing its components as modulators of immunosuppression and hormonal dynamics, testicular morphometry and its impact on gonadal histology. 12 male rabbits lop aged 4 months, were placed in four experimental groups were selected. Of the four treatments blood samples were obtained before each application of anti-GnRH biological hormonal analysis for LH, FSH, and testosterone, plus testis measurement of morphometry and histology….